Mistake as an unjust factor: autonomy and unjust enrichment - Seah, W (2015)
This thesis is about the law of mistake in the law of unjust enrichment. It argues that a particular, autonomy-based normative account explains and justifies the current substantive law of mistake, and goes on to suggest consequential resolutions for some of the remaining controversial areas of the law. The normative account is that the justification for recognising mistake as a reason for restitution – what makes the mistaken enrichment 'unjust' – is the value given to the personal autonomy of individuals in determining the terms on which their resources are disposed. That account explains why the law of unjust enrichment has an initial but not exclusive focus on the claimant's intention, including that it must be present, properly formed and properly effected; and for the law of mistake specifically, the account provides a coherent explanation for why the established or 'core' areas of the law appear the way they do. In relation to the still controversial areas of mistake, the same account suggests that: (i) a reasonable degree of uncertainty or doubt should deny an unjust enrichment action based on mistake; (ii) causative ignorance is neither a mistake nor should it be recognised as an unjust factor; (iii) voluntary dispositions should be considered unjust once causative mistake is established; and (iv) while the line between mistakes and mispredictions is blurred in certain circumstances, clear and sound resolutions can be structured on the basis of the autonomy-centred normative account.